Further evidence of validity of the Nursing Decision Making Instrument: an Italian validation study - Albanesi, Beatrice; Caruso, Rosario; Arrigoni, Cristina; De Benedictis, Anna; Baroni, Irene; Villa, Giulia; Dellafiore, Federica (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: This study aimed to provide the Italian version of the Nursing Decision Making Instrument (NDMI) and establish its content and face validity, construct validity, and reliability among Italian nurses. Methods: A three phases validation, methodological and cross-sectional study was realized. Phase one referred to the cultural-linguistic translation of the NDMI into Italian (i.e., I- NDMI). Phase two aimed to obtain a good level of content and face validity (cut-off <0.70). Phase three involved a cross-section data collection amongst Italian nurses in assessing the construct validity and reliability of the I-NDMI. Results: I-NDMI showed adequate content validity. Confirmatory factor analysis models supported the four-factorial structure of the I-NDMI (i.e., Intuition; Prevision; Assessment; Planning) in explaining data obtained from nurses. Moreover, the scale and each domain showed adequate internal consistency. Conclusions: This study constituted an advancement in the psychometric testing of the NDMI. Future research should identify specific decision-making processes and their determinants to allow theoretically grounded interventions to improve decision-making among nurses.